STRATEGI MEDIA RELATIONS PORES DUMAI DALAM MENGURANGI KEBAKARAN HUTAN DAN LAHAN DI DUMAI TAHUN 2016 - Agustian Maulana; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Forest and land fires in Dumai isenvironmental issueswhich has been in existence since 1997/1998 and continued until 2016. Up until now forest and land fires has become one of natural disasters which always occur in dumai and still can not be handled properly by the stakeholders, raising many questions by society about how the forest and land fires being handled which is a routine agenda in Dumai City. And aims to know how Dumai City Police Departement can manage relationships, develop strategies, and develop networks with mass media.This research uses qualitative method by using purposive sampling technique to get informant, with criteria of informant have experience in their field respectively more than five year, and the number of this research informants is four people.The purpose of this research is to know how to manage strategies, develop strategies, and develop networks with mass mediabyPublic Relations of Dumai City Police Departementrelated to forest and land firesthat happened in Dumai City. The result of this research to build and mantain good relationships with journalistsis not easy, because they are very busy people and has various kind of attitudes, and there are some obstacles such as lack of open communication between Public Relations of Dumai City Police Departement and mass media, but this can be used as input to Public Relations of Dumai City Police Departement. Various approaches taken by Public Relations of Dumai City Police Departement so every single news in mass media covered honestly, accurate and balanced by journalists. Based on the description above, the approach can be done with formally or informally. Each of the approaches has differences in treating journalists in formally or informally.